2021
DOI: 10.3390/horticulturae7100350
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multipurpose Core Collection of New Promising Iranian Pomegranate (Punica granatum L.) Genotypes Based on Morphological and Pomological Traits

Abstract: Establishment of a core collection, of limited size and better representation of the whole germplasm phenotypic diversity, is fundamental for fruit tree breeding programs from an economic and management points of view. To achieve this goal with pomegranate fruit trees, 221 genotypes were evaluated for 25 morphological and pomological traits during two successive years. Using the maximization strategy in Power Core software, 12 out of 221 pomegranate genotypes were selected for the new core collection, reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
14
2
Order By: Relevance
“…Previously developed pomegranate core collection size by Razi et al [33] with 25 morphological traits was 5.6% of the entire collection (225 genotypes) which is lower in size than the core collection obtained in this study. Kazemi et al [26] also developed a core collection of pomegranate based on the data of 12 SSR markers on 738 accessions, which comprised 34 accessions (about 4.61% of the total collection).…”
Section: Core Collection Constructioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Previously developed pomegranate core collection size by Razi et al [33] with 25 morphological traits was 5.6% of the entire collection (225 genotypes) which is lower in size than the core collection obtained in this study. Kazemi et al [26] also developed a core collection of pomegranate based on the data of 12 SSR markers on 738 accessions, which comprised 34 accessions (about 4.61% of the total collection).…”
Section: Core Collection Constructioncontrasting
confidence: 65%
“…The results of PCA of 100 pomegranate genotypes from Iran using 40 morphological descriptors indicated that the first three components explained 22.24% of the variance [31] which was less than our study. Principal factor analysis of 25 morphological traits on 221 Iranian pomegranate genotypes classified traits in seven main groups which the first three principal components explained about 48.58% of the cumulative variance [33]. Among the traits used in that study, fruit skin color, fruit shape, flower position, and fruitful flower percentage appeared as the best traits to differentiate the pomegranate genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s, Frankel (1984) and Brown (1989) proposed the concept of core collection to maximize the genetic information of a population with a small number of resources [25,26]. Genetic diversity is enriched, and the number of resources and management costs are reduced in this concept [27,28]. The construction of core resource banks at an early stage is based on phenotypic trait evaluation, which is simple and operable, but low in accuracy due to its vulnerability to environmental influences [29].…”
Section: Introductionmentioning
confidence: 99%
“…Both morphological and molecular markers can be used to construct a core collection. The construction of core collections based on morphological, physiological, and biochemical traits has been reported for pomegranate ( Punica granatum L.) [ 9 ], Huangxinzimu ( Catalpa fargesii f.duclouxii ) [ 10 ], and Ziziphus mauritiana Lam. [ 11 ].…”
Section: Introductionmentioning
confidence: 99%